ChemInform Abstract: A Convenient Metal‐Free Reagent for the Generation and Capture of Trifluoromethanethiol. Issue 14 (8th April 2014) - Li, Shi‐Guang; Zard, Samir Z.
Abstract Both newly synthesized reagents (III) and (IV) are proved to be valuable for introducing the CF3 or CF3S‐ motifs trough radical and ionic mechanisms, respectively.